The pragmatics of celebrity fan wars: A case study of Wizkid and Davido fans on X - David Oluwatobi Esuola; Tayo Adebayo; Temitope Michael Ajayi (Yayasan Mitra Persada Nusantara, 2025)
Celebrity rivalry refers to a situation in which two or more well-known public figures, typically from the entertainment, sports, or fashion industries, are perceived to be in conflict or competition with one another. Even though scholars have explored the celebrity rivalry between Wizkid and Davido, studies on the rivalry among their fans remain underexplored. Thus, from a qualitative research perspective, this study is a pragma-discursive analysis of the online interactions between the fans of Wizkid known as (FC) and fans of Davido known as (30BG). The data were examined using Henry Jenkins (1992) Fandom theory. Findings show that fans of both artists deploy impoliteness to foreground their celebrity’s industry, how their fans project the industry’s success over the other artist and financial supremacy over the other celebrity, and how their favorite celebrity is projected as richer than the other celebrity. Further studies can be done on comparing artists of different countries.